MODERN HUMANISM: BETWEEN INDIVIDUALISM AND COLLECTIVISM - Nikolay Petrovich Medvedev (Вестник Северо-Кавказского федерального университета)
In the article the necessity of working out a new morality, and it will become the basis of civil consolidations the face of the increasing dangers and threats for human urban civilization. The article reveals the failure to use to justify the morality antihumanisms, ideas existencealisms, pragmatisms, liberalisms in its extremely individualistic form libertarianisms.